2017
DOI: 10.1017/s0263574717000340
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of an origami-based three-finger manipulator

Abstract: SUMMARYThis paper describes a new robotic manipulator with three fingers based on an origami twisted tower design. The design specifications, kinematic description, and results from the stiffness and durability tests for the selected origami design are presented. The robotic arm is made of a 10-layer twisted tower, actuated by four cables with pulleys driven by servo motors. Each finger is made of a smaller 11-layer tower and uses a single cable directly attached to a servo motor. The current hardware setup su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…They employed a silicone elastomer (Dow Corning Sylgard 186) to realize an entirely compliant structure. Other researchers also demonstrated soft cable‐driven grippers by placing cables inside an elastomeric bag, textiles, and origamis, similar to continuum tendon‐driven manipulators . Calisti et al demonstrated the grasping of a pencil and screws by a tendon‐driven elastomeric manipulator inspired by the Octopus arm (Figure h), which was later implemented in a robot capable of locomotion and object manipulation .…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…They employed a silicone elastomer (Dow Corning Sylgard 186) to realize an entirely compliant structure. Other researchers also demonstrated soft cable‐driven grippers by placing cables inside an elastomeric bag, textiles, and origamis, similar to continuum tendon‐driven manipulators . Calisti et al demonstrated the grasping of a pencil and screws by a tendon‐driven elastomeric manipulator inspired by the Octopus arm (Figure h), which was later implemented in a robot capable of locomotion and object manipulation .…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…It generates continuous bending, twisting, and linear motions via structural reconfiguration, and its linear extension-to-contraction ratio can reach over 4:1. Utilizing these unique structural properties, twisted towers were used for various robotic applications, including reconfigurable origami wheels [1], a crawling robot [2], and a robotic manipulator arm [3]. In particular, the three-finger robotic manipulator presented in [3] used the hand-folded twisted towers for its arm and fingers, demonstrating object manipulation capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Kresling origami structure, Pagano et al designed a crawling robot that performs both linear and turning movements [21]. Jeong et al designed a cable-driven three-finger robot based on the twisted tower origami structure, which has the potential to grab fragile items [22]. Fang et al designed an earthworm-like robot based on an origami ball that could achieve effective locomotion [23].…”
Section: Introductionmentioning
confidence: 99%